Morphometric Measurements of Root Anatomic Areas of Maxillary First Premolar Teeth in a Representative Nepalese Population - Pandey, Nashib; Koju, Sushmit; Bhattarai, Rosina; Jha, Kanistika; Shakya, Merina; Roy, Prabash; Chaulagain, Rajib (Journal of College of Medical Sciences-Nepal, 2024)
Background The prognosis of furcation involved maxillary first premolar is typically guarded to poor. The presence of concavities in the root trunk and the positioning of the roots in the buccal and palatal regions of the teeth are responsible for its challenges during instrumentation and control plaque. We aimed to access the presence of concavities on the root surface as well as morphometric measurement of the root trunk dimensions in the maxillary first premolar teeth in Nepalese population. Methods A cross-sectional quantitative study was conducted in the Department of Periodontics and Oral Implantology, College of Medical Sciences (CoMS). Extracted Maxillary first premolar teeth were evaluated for the number of roots, morphometric measurement of the root trunk, root divergence, and root length. The presence of concavities was recorded on the mesial and distal root surface at cervical, middle, and apical thirds of the root. Results The overall mean root trunk length was less on the mesial aspect than on the distal aspect (6.39 ± 2.54 and 8.08 ± 3.48 respectively). The prevalence of root surface concavity on the cervical third at the mesial aspect (90 %) was found to be higher than in the distal aspect (15%) Conclusions Owing to the higher prevalence of root surface concavity on the cervical third of mesial aspect, use of mini-bladed curettes is recommended for the effective root surface debridement of the periodontally involved maxillary first premolar tooth. Patients with periodontally involved maxillary first premolar should be advised to use interdental brushes rather than dental floss.